PESANTREN DAN PENANAMAN SIKAP ANTI KORUPSI - Fathoni, Tamrin (Fakultas Syariah INSURI Ponorogo, 2019)
The purpose of this study is to explore the role of pesantren in instilling anti-corruption attitudes. Pesantren is empirically known as a successful institution in developing quality education, especially in the field of religion. In the midst of a number of compliments received from pesantren, there is criticism that must reflect the pesantren, that pesantren are considered to have not succeeded in perfectly educating students who have strong personalities in anti-corruption. That criticism is not without foundation. The ministry of religion which incidentally is the headquarters of the students, is also known as one of the ministries which often ministers stumble over corruption cases. Even though they are not a few who in their daily lives work as preachers and obligatory worshipers, and can even be categorized as scholars. This study uses qualitative research library type. Data collection by identifying discourses from books, papers or articles, journals, newspapers, internet (websites), and other information that is still related to pesantren studies. Data analysis uses descriptive analysis and critical analysis. Descriptive analysis is collecting and compiling data then the data is analyzed. Meanwhile, critical analysis is the interpretation of the text and addressing the meaning behind events scientifically. The results showed the need for pesantren stakeholders to reaffirm the pesantren culture to instill anti-corruption in their students. especially through his students. Because students with their pesanten culture (a) have a simple tradition of life an absolute requirement to be a pioneer of anti-corruption; (b) has strong religious insight, and (c) deep-rooted tradition amar ma'ruf nahi munkar.